A Novel Approach to Limit Chemical Deterioration of Gilthead Sea Bream(Sparus aurata)Fillets: Coating with Electrospun Nanofibers as Characterized by Molecular, Thermal, and Microstructural Properties - Ceylan, Zafer; Sengor, Gulgun F. Unal; Yilmaz, Mustafa Tahsin (WILEY, 2017)
Coating of sea bream fillets with thymol loaded chitosan based electrospun nanofibers (TLCN) and chitosan based nanafibers (CN) has been presented a novel approach to delay chemical deterioration. We assessed CN and TLCN with respect of scanting of total volatile basic nitrogen (TVBN), trimethylamine (TMA), thiobarbituric acid (TBA) deterioration during cold storage condition. Electrospinning process was applied to obtain TLCN and CN. Both of nanofibers obtained from biopolymer and bioactive material were cylindrical, smooth, beadless. Thermal, molecular, zeta potential (ZP), and surface properties of the groups were investigated, revealing that CN indicated molecular interactions with thymol in nanofibers, reduce in physical properties of these structures, thermal decomposition (an alteration in mass of CN and TLCN at temperatures below 190 degrees C, corresponding to 20.53% and 19.97%, respectively) and also dispersion stabilities ( potential) of CN and TLCN were determined 33.68 +/- 3.35 and 21.85 +/- 1.96 mV, respectively. TVBN and TMA stability analyses demonstrated that CN and TLCN were both effective in delaying chemical deterioration of fish fillets, furthermore TLCN was more effective against chemical deterioration. TBA analyses results of fish fillets indicated that CN and TLCN delayed rancidity in fish meat as compared to control group samples. The presented study results suggested that coating of the sea bream fillets with CN and TLCN would be a promising approach to delay the chemical deterioration of fish fillets.
Keywords: chemical deterioration; combining of chitosan and thymol; electrospun nanofiber; fish qualitycoating with nanofiber; MODIFIED ATMOSPHERE; SHELF-LIFE; CHITOSAN; QUALITY; FISH; BACTERIA; ICE; Food Science & Technology